Insurance Agreement Through A Digital System In The Framework Of Consumer Protection Approach For Insured Participants - Rully Syahrul Mucharom; Fatkhul Muin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of the study: This study focuses on legal developments regarding digital agreements that occur in insurance offerings to the public and are considered a legally valid written agreement. Law No. 40 of 2014 concerning Insurance establishes the basis of insurance as an agreement between two parties, namely the insurance company and the policyholder, which serves as the basis for the insurance company's premium receipt as compensation. With the development of technology, digital insurance offerings are often conducted on the basis of a valid insurance agreement. Electronic insurance policies can be used and are recognized as stipulated in Article 21 Paragraph (1) of OJK Regulation No. 23/POJK.05/2015 concerning Insurance Products and Marketing of Insurance Products. Consumer protection in insurance in the form of digital agreements is necessary. Materials and Methods: This study focuses on qualitative methods with a legal approach, conducting an in-depth analysis of insurance agreements through digital systems within the framework of a consumer protection approach for insurance participants. Results: The development of technology and information has driven behavioral changes in the business world, one of which is the insurance business. Therefore, aspects of Law No. Law No. 40 of 2014 concerning Insurance and Law No. 8 of 1999 concerning Consumer Protection must be aligned. Conclusions: This research focuses on Law No. 40 of 2014 concerning Insurance and Law No. 8 of 1999 concerning Consumer Protection. Therefore, in insurance, the interests of insurers must be safeguarded and protected.